Gastric Antral Vascular Ectasia: A Case Report and Literature Review - Alkhormi, Abdulrahman M. (J Transl Int Med, 2018)
Gastric antral vascular ectasia (GAVE) is a rare but an important cause of upper gastrointestinal bleeding (UGIB) and commonly presents as occult bleeding that manifests as iron deficiency anemia (IDA). GAVE is commonly associated with chronic illnesses, most frequently liver cirrhosis and connective tissue diseases. The pathogenesis of GAVE is still obscure, and many hypotheses such as mechanical stress, hormonal factors, and autoimmune factors, have been proposed. Upper gastrointestinal endoscopy has a major role in the diagnosis and treatment of GAVE.